2017
DOI: 10.5539/ies.v10n9p9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Students from the Department of Computer Education and Instructional Technologies Regarding the Concept of Curriculum

Abstract: In the study, the purpose was to determine the perceptions of students from the department of Computer Education and Instructional Technologies regarding the concept of curriculum. The participants of the study conducted with the phenomenology research design were 212 preservice teachers. The research data were collected via document analysis and interviews. For the analysis of the data, the inductive content analysis method was used. The results revealed that the preservice teachers perceived the concept of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…It can be inferred that the participants think of the PSC as a factor that shapes the future to achieve the determined goals. The finding related to this conflicts with the findings of Yeşilpınar Uyar (2017) because the researcher concluded that the knowledge level of teacher candidates about the curriculum is partially sufficient in his study.…”
Section: Conclusion and Discussioncontrasting
confidence: 61%
“…It can be inferred that the participants think of the PSC as a factor that shapes the future to achieve the determined goals. The finding related to this conflicts with the findings of Yeşilpınar Uyar (2017) because the researcher concluded that the knowledge level of teacher candidates about the curriculum is partially sufficient in his study.…”
Section: Conclusion and Discussioncontrasting
confidence: 61%